Modeling biogenic secondary organic aerosol (BSOA) formation from monoterpene reactions with NO3: A case study of the SOAS campaign using CMAQ. (July 2018) - Qin, Momei; Hu, Yongtao; Wang, Xuesong; Vasilakos, Petros; Boyd, Christopher M.; Xu, Lu; Song, Yu; Ng, Nga Lee; Nenes, Athanasios; Russell, Armistead G.
Abstract: Monoterpenes react with nitrate radicals (NO3 ), contributing substantially to nighttime organic aerosol (OA) production. In this study, the role of reactions of monoterpenes + NO3 in forming biogenic secondary organic aerosol (BSOA) was examined using the Community Multiscale Air Quality (CMAQ) model, with extended emission profiles of biogenic volatile organic compounds (BVOCs), species-specific representations of BSOA production from individual monoterpenes and updated aerosol yields for monoterpene + NO3 . The model results were compared to detailed measurements from the Southern Oxidants and Aerosol Study (SOAS) at Centreville, Alabama. With the more detailed model, monoterpene-derived BSOA increased by ∼1 μg m −3  at night, accounting for one-third of observed less-oxidized oxygenated OA (LO-OOA), more closely agreeing with observations (lower error, stronger correlation). Implementation of a multigenerational oxidation approach resulted in the model capturing elevated OA episodes. With the aging model, aged semi-volatile organic compounds (ASVOCs) contributed over 60% of the monoterpene-derived BSOA, followed by SOA formation via nitrate radical chemistry, making up to 34% of that formed at night. Among individual monoterpenes, β-pinene and limonene contributed most to the monoterpene-derived BSOA from nighttime reactions. Highlights: Integrated advanced modeling approaches, detailed field measurements and results of chamber studies of SOA yields. Quantification of the contribution of monoterpene-formed BSOA via NO3 chemistry to form organic aerosol (OA) by species. Monoterpenes + NO3 contributed significantly to nocturnal OA via biogenic-anthropogenic interactions. Multigenerational-oxidation led to OA more similar to the observations. Results suggest daytime monoterpene emissions are higher than BEIS calculates while emissions at night should be lower.